Progress in the application of Enterococcus faecium in animal husbandry - Liu, Zhi-lin; Chen, Yun-jiao; Meng, Qing-lei; Zhang, Xin; Wang, Xue-li (Frontiers in Cellular and Infection Microbiology, 2023)
As a probiotic, enterococcus faecium (E. faecium) has the characteristics of high temperature resistance, gastric acid resistance, bile salt resistance, etc. It can also effectively improve animal performance and immunity and improve the animal’s intestinal environment, so in recent years it has been more widely used in the livestock industry. However, due to the improper use of antibiotics and the growing environmental stress of strains, the drug resistance of enterococcus faecium has become more and more serious, and because some enterococcus faecium carry virulence genes, leading to the emergence of pathogenic strains, its safety issues have been widely concerned. This paper focuses on the biological characteristics of enterococcus faecium, the application of this bacterium in animal husbandry and the safety issues in its use, with a view to providing a reference for the application of enterococcus faecium in the development of animal husbandry.